El desarrollo del lenguaje en los niños de 3, 4 y 5 años de edad y la influencia de los entornos familiar, social y educativo - Miriam Rosa Baylón Mendoza (Tesis (Lima), 2023)
Language development is progressive and starts from the first years of life. The fullness of the development of linguistic abilities, at the level of expression, comprehension and use of language, will depend on the genetic bases of each child and on the communicative interaction at home and in different environments. It is important to identify the most relevant aspects during the developmental period of language in order to prevent and timely address situations that could interfere with the development of language skills in children. Considering Noam Chomsky’s proposal, the child achieves the acquisition of the mother tongue through a cognitive process that allows the development of linguistic competence. After going through intermediate states and receiving linguistic stimuli in a community, the child internalizes the grammar of the language of his community, reaches a stable state and, consequently, will be able to produce and understand linguistic messages.